Comparação de ferramentas de análise de dados para uso no marketing digital - Bertãozini, Bruna da Silva Magalhães (Universidade Federal de São Carlos, 2024)
This paper focuses on the importance of data analysis in the field of digital marketing and choosing the most appropriate data analysis tool to optimize marketing strategies. The study compares three popular data analysis tools - Google Analytics, Adobe Analytics and Mixpanel - in terms of features, advantages and disadvantages. The purpose is to provide valuable perspectives that can help companies make accurate decisions when choosing the most appropriate data analysis tool for their demands. Emphasizing the context of digital marketing today and the impact of data analysis tools on everyday life.
Comparison of data analysis tools for use in digital marketing
Keywords: Análise de dados; Data analysis; Marketing digital; Digital marketing; Google Analytics; Adobe Analytics; Mixpanel; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO